The potential of health as a theoretical framework for nursing - Alves , Marcelo da Silva (Seven Editora, 2023)
It proposes a nursing theory based on Health Potentials. This reference works with the humanistic, phenomenological and existential issues of nursing from a post-modern perspective. It aims to be a reference for nurses and nursing students to develop the Systematization of Nursing Care (SAE) based on a simple, far-reaching reference, centered on the demands and expectations of clients, families and communities. It is hoped that this framework will be a facilitator, due to its uniqueness and simplicity of understanding and description, so that nursing can understand the importance of systematizing nursing care based on a theoretical reference focusing on the subjects in their own contexts of life and existence. The theoretical proposition, as well as its paradigms and mataparadigms, meet the ideological determinants of the Brazilian health system, promoting the inclusion of clients, families and communities in their therapeutic plans, overcoming the hard biomedical model and promoting care where the subjectivation of the subjects is the central axis of all actions, values and concepts. DOI:https://doi.org/10.56238/sevened2023.004-030